Implementing data governance to enhance data management at higher institution: UiTM data governance framework - Kamarulzaman, Mohd Ridwan; Ismail, Ahmad Nizam; Abdul Kadir, Irwan Kamarudin; Mazlan, Mazwani Ayu; Mohd Yunos, Alwi (Faculty of Information Management, 2025)
Data management has become a critical focus in higher education institutions due to the increasing reliance on digital technologies for both academic and administrative functions. The concept of data governance plays a pivotal role in managing the complexities of data within these institutions. This paper explores the implementation of data governance frameworks in higher education institutions, specifically UiTM, using the DAMA DMBOK framework as the methodology. The paper provides insights into UiTM's experience in implementing data governance to increase accountability and improve data quality across different departments within the university. The findings highlight how UiTM’s data governance framework has been instrumental in addressing data challenges, ensuring accountability, and enhancing data quality at an institutional level." Data management has become a critical focus in higher education institutions due to the increasing reliance on digital technologies for both academic and administrative functions. The concept of data governance plays a pivotal role in managing the complexities of data within these institutions. This paper explores the implementation of data governance frameworks in higher education institutions which is UiTM. The paper provides insight on data governance based on UiTM experience in implementing data governance to increase accountability and improve data quality across different departments within universities.